THE EFFECTIVENESS OF GIVING SOY MILK TO INCREASING HAEMOGLOBIN (Hb) LEVELS IN ANEMIA ADOLSCENT IN THE WORK AREA OF THE CIHIDEUNG COMMUNITY HEALTH CENTER TASIKMALAYA CITY - Syifa Haidar Rahmani; Uly Artha Silalahi; Meti Widiya Lestari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The World Health Organization (WHO) states the prevalence of anemia in developing countries at 30-48%. Based on Riskesdas 2018, the prevalence of adolescent anemia in Indonesia is 32. The prevalence of anemia in the working area of ​​the Cihideung Health Center is 36.61%. This study aims to determine the effectiveness of soy milk administration against increased levels of haemoglobin (hb) in anemic adolescent girls. This study uses Quasy-Experiment design with Pretest and Posttest Control Group design. This research carried out in the working area of the Cihideung health center, Tasikmalaya City. The population in this study was adolescent girls aged 13-14 years who had anemia as many as 30 adolescents. The sampling technique to be used is total sampling. The data analysis used was univariate analysis and Wilcoxon bivariate analysis and Mann Withney difference test. The results of the study found that the average Hb level of the intervention group before treatment was 10.833, after treatment increased to 13.267, so there was an increase of 2.434. In the control group before treatment was 10,987, after treatment increased to 12,593, resulting in an increase of 1,606. Wilcoxon statistical test was carried out, the intervention group obtained results (P = 0.001) and the control group (P = 0.001). Different test was carried out using Mann Withney's analysis, the results of the P Value value of 0.011. It can be concluded that there is a significant difference in average Hb levels between the intervention group and the control group